Ni/MgO-MgAl2O4 Catalysts with Bimodal Pore Structure for Steam-CO2-Reforming of Methane - Kim, Byung-Hyuk; Yang, Eun-Hyeok; Moon, Dong Ju; Kim, Sang Woo (American Scientific Publishers, 2015)
The bead type MgO-MgAl2O4 catalyst supports with bimodal pore structures were fabricated via an extrusion molding of gels derived from the precursor mixture of mesoporous MgO particles and aluminum magnesium hydroxide, followed by heat treatment. To investigate the effect of macro pore structures on the catalytic activity of the Ni/MgO-MgAl2O4 catalysts in the steam and carbon dioxide reforming of methane (SCR), two kinds of the catalysts with largely different macro pore volumes and sizes but nearly the same meso pore volume and size were compared. The bimodal catalyst with a large macro pore size and volume exhibited a highly enhanced CO2 conversion from 22.3 to 37.1% but a slightly reduced CH4 conversion from 95.3 to 92.1% at the same feed ratio. The SCR results show that the large macro pores can lead to a highly enhanced mass transfer rate of CO2 absorption into the pore channels of the magnesium alumina spinel.